PERFORMANCE APPRAISALS IN THE OR: EVERYONE’S BUSINESS - Porteous, Joan (Operating Room Nurses Association of Canada Journal, 2006)
Performance appraisals affect everyone. Perioperative nurses often participate in staff orientations and act as preceptors for other learners. Nurses also participate in their own performance appraisal process. This article discusses performance appraisal forms and performance interview processes. Examples of a performance appraisal form design and performance indicators for perioperative nurses are included. Potential problems with performance appraisals are identified and the impact of Canadian law on performance appraisals is discussed.